Clinical Nutritional Study on Prevention and Treatment of Lifestyle-related Disease: 2002's JSNFS Award for Excellence in Research - Itoh, Kazue (Nippon Eiyo Shokuryo Gakkaishi, 2003)
Clinical and nutritional studies on the prevention and treatment of hypertension and hyperlipidemia in humans have been ongoing for the past 20 years. Such studies have focused on (1) the effect of high oral potassium levels and a large amount of magnesium supplementation on blood pressure, serum lipid levels and related variables in apparently healthy subjects, (2) the comparative epidemiology of hypertension in Nepal, (3) the association between blood pressure and insulin resistance in obese women, and (4) the effect of weight loss on blood pressure and serum leptin concentrations, which are both closely correlated with insulin and insulin-related variables, as well as the correlation between weight loss-induced blood pressure changes and the level of insulin, total abdominal fat and 24-h urinary norepinephrine excretion as an indices of sympathetic nervous system activity. Non-pharmacological treatment of these conditions by regulating the dietary intake of potassium, magnesium and weight loss, is now considered to be of importance.